Farmakologia. Podręcznik dla studentów i absolwentów kierunków medycznych - Nowakowska, Elżbieta - red.; Kopciuch, Dorota; Kotlęga, Dariusz; Sulimiera-Michalak, Sylwia; Michalak, Lidia Magdalena; Heller, Alfred; Kieres, Karolina; Zaprutko, Tomasz; Suchecki, Zbigniew; Hoffmann, Karolina; Harbich, Maciej; Paczkowska, Anna; et al. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Pharmacology, a textbook for medical students and graduates, edited by Elżbieta Nowakowska, is a valuable source of information on the mechanisms of action of specific drug classes and treatment regimens for specific disease entities. It addresses the need for individualized treatment based on the characteristics of a given patient population, highlights the problem of off-label drug use, and underlines the important issue of adverse drug reactions. Legal aspects related to the prescription of medications by nurses and midwives are discussed extensively. Each chapter of the textbook contains a set of test questions, helping students verify their knowledge before the exam.
Keywords: aspekty prawne dotyczące ordynowania leków; farmakologia ogólna; farmakoterapia w chorobach cywilizacyjnych; legal aspects of drug prescribing; general pharmacology; pharmacotherapy in lifestyle diseases